Something to look forward to [large type] - Flagg, Fannie (Random House Large Print, 2025)
"Fannie Flagg once said that what the world needs now is a good laugh. And that is what she gives us in these thirty warmhearted, often hilarious, always surprising stories about Americans finding clever ways of dealing with the curveballs life throws at us. We meet Velma from Kansas, a loving great-grandmother who struggles to bridge the generational divide with her great-grandchild in California. Why, for instance, does her great-grandchild sign letters to Velma with "(they/them)"? We cheer for Helen, in Ithaca, New York, who takes an audacious course of action when her husband leaves her for a younger woman. Four men in Bent Fork, Wyoming, make a bold decision after learning that the café where they eat breakfast every day is about to be sold to a stranger from out of town. And observing them all is Special Agent Frawley, an odd visitor from another planet, sent to Earth to figure out what makes human beings tick, only to fall in love with one of them--and with her cat"--